Sistem Prediksi Pertumbuhan Ekonomi Kabupaten Musi Rawas, Kabupaten Musi Rawas Utara Dan Kota Lubuklinggau Dengan Metode Regresi Linier - Andri Anto Tri S; Armanto Armanto; Harma Oktafia Lingga Wijaya; Wisdalia Maya Sari (Jurnal Sistem Komputer dan Informatika (JSON), 2022)
The economic condition of a region in each period can increase or decrease by looking at changes in goods and services. An increase in economic activity is a process of changing economic conditions that occur in an area on an ongoing basis to get to a better state for a certain period of time. Economic growth is a benchmark in achieving the development of economic conditions in a region so that it has an impact on increasing people's welfare. South Sumatra's economic growth in the first quarter of 2021 improved compared to the previous quarter. Similar to economic growth in South Sumatra Province, the districts and cities in it (Musi Rawas Regency, North Musi Rawas and Lubuklinggau City) also experienced ups and downs of economic growth. With the current ups and downs of economic growth, Musi Rawas Regency, North Musi Rawas and Lubuklinggau City need accurate information about the picture of economic growth in the future, this is intended to be able to prepare various policies or actions so that the level of the economy in Musi Rawas Regency, Musi North Rawas and Lubuklinggau City can be increased. Based on this problem, Musi Rawas Regency, North Musi Rawas and Lubuklinggau City need a prediction system in order to see a picture of economic growth in the future. The purpose of this study is to design a prediction system that can predict the rate of economic growth in Musi Rawas Regency, North Musi Rawas and Lubuklinggau City. The method used in the prediction system is a simple linear regression method, the use of a simple linear regression method in this study due to the limited time of the study and used to determine the direction of the relationship between the independent variable and the dependent variable, whether it has a positive or negative relationship and to predict the value of the dependent variable if the value of the independent variable increases or decreases.